2007
DOI: 10.1080/09593332808618874
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Orange G by Laccase: Fungal Versus Enzymatic Process

Abstract: Biodegradation of the Orange G azo dye by pellets of Trametes versicolor in a fluidized bioreactor operating under conditions of laccase production was studied. The percentage of decolorization obtained was 97% in batch mode and both the biomass and the broth, were colorless. In vitro degradations carried out with purified commercial laccase from Trametes versicolor demonstrated that laccase is able to degrade the dye. In spite of the high level of decolorization reached in both processes, an important differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…As a result, higher removal efficiency was observed for most selected PhACs in the presence of redox mediators (ABTS or HBT) compared with those in the absence of mediators. The degradation tendency observed in this study is relatively consistent with those reported in the literature (Rodríguez et al, 2004;Tamagawa et al, 2005;Maruyama et al, 2006;Auriol et al, 2007;Canas et al, 2007;Casas et al, 2007), wherein they found that fungal laccase can oxidize a variety of organic compounds in the presence of a redox mediator, such as HBT or ABTS. However, the degradation spectrum in the presence of redox mediators was still mainly dependent on the characteristics of target compounds.…”
Section: Degradation Of Phacs In the Presence Of Mediatorssupporting
confidence: 81%
“…As a result, higher removal efficiency was observed for most selected PhACs in the presence of redox mediators (ABTS or HBT) compared with those in the absence of mediators. The degradation tendency observed in this study is relatively consistent with those reported in the literature (Rodríguez et al, 2004;Tamagawa et al, 2005;Maruyama et al, 2006;Auriol et al, 2007;Canas et al, 2007;Casas et al, 2007), wherein they found that fungal laccase can oxidize a variety of organic compounds in the presence of a redox mediator, such as HBT or ABTS. However, the degradation spectrum in the presence of redox mediators was still mainly dependent on the characteristics of target compounds.…”
Section: Degradation Of Phacs In the Presence Of Mediatorssupporting
confidence: 81%
“…Degradation of these compounds in azo dyes is a challenge in current research. Microbial enzymes are capable of removing phenolics and aromatic amines present in the azo dyes (Claus 2003; Casas et al 2007). The enzyme laccase, has enormous biotechnological applications such as in paper pulp bleaching, decolorization of synthetic dyes, wine clarification, fruit juice processing, bioremediation, ethanol production, biosensors, biofuel cells, organic synthesis and drug synthesis (Mayer and Staples 2002; Hadzhiyska et al 2006; Zhu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained percentage of decolourization was 97% in only 20 h. As high as 3500 AU/L of laccase was determined, while no MnP activity was detected. Better results were obtained this way compared to In Vitro experiments with commercial purified laccase from T. versicolour (Casas et al, 2007). The batch and continuous operation mode of a 1.5-L bubble column bioreactor were used for the cultivation of T. versicolour in the pellet form and degradation of Grey Lanaset G metalcomplex dye.…”
Section: Bubble Column Bioreactormentioning
confidence: 99%
“…Selected references from the last decade for laboratory reactors with volumes larger than 1.0 L are briefly presented below. Libra, 2003Leidig, 1999Casas, 2007Blanquez, 2004Zhang, 1999Tavčar, 2006Ge, 2004Tavčar, 2006Trošt, 2010 Yang, 2009 Hai, 2008Gao, 2009 Table 5. Fungal bioreactors for degradation and decolourization of dyes…”
Section: Bioreactors For Fungal Degradation and Decolourization Of Dyesmentioning
confidence: 99%